2014
DOI: 10.24095/hpcdp.34.4.03
|View full text |Cite
|
Sign up to set email alerts
|

Developing injury indicators for First Nations and Inuit children and youth in Canada: a modified Delphi approach

Abstract: Introduction The purpose of this research was to take the initial step in developing valid indicators that reflect the injury issues facing First Nations and Inuit children and youth in Canada. Methods Using a modified-Delphi process, relevant expert and community stakeholders rated each indicator on its perceived usefulness and ability to prompt action to reduce injury among children and youth in indigenous communities. The Delphi process included 5 phases and result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 5 publications
0
8
0
Order By: Relevance
“…These different consequences of unintentional injuries are important to measure to assist community leaders in determining priorities for actions, develop appropriate strategies and services, and evaluate the impact of such activities. Injury prevention indicators for Inuit children and youth have been identified through an extensive process by the First Nations and Inuit Children and Youth Injury Indicators Project Task Group, with the aim to provide a framework for collecting data[ 27 ]. Qanuippitaa?…”
Section: Discussionmentioning
confidence: 99%
“…These different consequences of unintentional injuries are important to measure to assist community leaders in determining priorities for actions, develop appropriate strategies and services, and evaluate the impact of such activities. Injury prevention indicators for Inuit children and youth have been identified through an extensive process by the First Nations and Inuit Children and Youth Injury Indicators Project Task Group, with the aim to provide a framework for collecting data[ 27 ]. Qanuippitaa?…”
Section: Discussionmentioning
confidence: 99%
“…For determining provincial injury prevention priorities, the BCIPC undertook a rigorous mixed-method three-round modified Delphi approach adapted from the methods described by Lindsay et al [41] and successfully implemented by Pike et al, in a Canadian context [42,43]. In round 1 of the modified Delphi, a prioritization matrix was used to rate major mechanisms of injury.…”
Section: Priority Setting Processmentioning
confidence: 99%
“…As Angell (2012) writes, it is not an over-stated fact that the health status of First Nations, Inuit and Métis people falls below that of the rest of the Canadian population. According to Health Canada (2011), and Pike MacPherson and McDonald (2010), injuries within First Nations communities are the leading cause of death, estimated at twice the national average. Furthermore,there is limited research focusing on vehicle driver, passenger, and pedestrian safety with this population (Angell 2012).…”
Section: Participatory Research and Ethical Engagement In Coast Salis...mentioning
confidence: 99%
“…Indeed, a Transport Canada (2003 study involving three First Nations communities in Manitoba revealed very low rates of childseat use, particularly in school-aged children. The First Nations and Inuit Children and Youth Injury Indicators Working Group noted that vehicle crashes are the main cause of injury and death of Aboriginal people under 25 years of age (Pike et al, 2010). With the aim to better understand and reduce the risk of injuries and fatalities from all manner of vehicles, Angell's prevention initiative in collaboration with researchers and First Nations, Inuit and Métis peoples and communities is geared to address this gap in knowledge and to create conversations within Indigenous peoples about how best to respond in partnership to deal with these ongoing challenges.…”
Section: Participatory Research and Ethical Engagement In Coast Salis...mentioning
confidence: 99%